EUS-guided Transgastric Drainage of a Post-pancreatectomy Abdominal Fluid Collection Using a Lumen-apposing Metal Stent. Issue 4 (October 2017) - Trindade, Arvind Julius; Rahman, Merajur; Inamdar, Sumant; Bitton, Samuel
Abstract : Supplemental Digital Content is available in the text